PREVALENCE AND ASSOCIATED RISK FACTORS OF ANKLE SPRAIN AMONG VOLLEYBALL PLAYERS IN PESHAWAR SPORT COMPLEXES AND TECHNICAL COLLEGE PESHAWAR: A CROSS SECTIONAL SURVEY (The Research of Medical Science Review, 2025)
Background: Ankle sprain is a tear of ligaments of the ankle that hold the ankle in place and connect it with other bones in leg and foot. It occurs when foot suddenly rolls or twists, forcing the ankle joint out of its normal position. Swelling and bruising can occur due to tear in ligaments. Walking, running, jumping or even wearing improper footwear can cause this type of injury. Objective: The aim of the study was to find the prevalence and associated risk factors of ankle sprain among volleyball players in Peshawar sports complexes and technical college Peshawar. Methods: A cross-sectional survey was carried out in Peshawar Sports Complex, Qayyum Sports Complex and Technical college Peshawar. A total of 210 participants were added to the study. Ankle Sprain were checked by FADI and FADI Sports. Significance and association were calculated by using SPSS 25.0. The demographic statistics were calculated, and frequency tables were made. Results: Our survey aimed to assess the prevalence and associated risk factors of ankle sprain among volleyball players. The age (P=0.000), BMI (P=0.000), footwear(P=0.000), jumping(P=0.000), landing(P=0.000) were found to be significantly associated with FADI and FADI sports. Conclusion: This study confirms that ankle sprain significantly affects the performance of volleyball players.